2015
DOI: 10.1007/s00417-015-3115-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of retinal wall-to-lumen ratio by adaptive optics retinal camera: a clinical research

Abstract: The technique of AO retinal imaging allows a direct measurement of the retinal vessel wall and lumen diameter with good intra-observer variability. Age, arterial hypertension and an elevated BMI level are significantly associated with an increased WLR. The wall-to-lumen ratio measured by AO can be used to detect structural retinal microvascular alterations in an early stage of remodeling processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 40 publications
4
54
0
3
Order By: Relevance
“…Concerning arterioles, previous imaging methods had already detected enlargement with age [30]. More recently, in line with our findings, studies using AOC showed the increase of WLR with age in small populations [31]. In addition, WLR anatomical components have been studied individually [6] indicating that aging is associated with a significant increase in wall thickness, whereas internal diameter remained invariant.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning arterioles, previous imaging methods had already detected enlargement with age [30]. More recently, in line with our findings, studies using AOC showed the increase of WLR with age in small populations [31]. In addition, WLR anatomical components have been studied individually [6] indicating that aging is associated with a significant increase in wall thickness, whereas internal diameter remained invariant.…”
Section: Discussionsupporting
confidence: 90%
“…45 This phenomenon is supported by the measurement of retinal vessel wall using adaptive optics retinal camera, and age was associated with the increased wall-to-lumen ratio (WLR) of the retinal arterioles. 46 A significant increase of WLR was found in the middle age group (40–59 years), compared to young group (20–39 years). In the G3 group in the present study, there was no significant drop of the retinal vessel density, possibly indicating intact tissue perfusion.…”
Section: Discussionmentioning
confidence: 82%
“…Using AO retinal imaging, WLR can be measured non‐invasively and has been shown to increase with mean blood pressure, body mass index and age . The WLR in healthy individuals is highly predictable from the size of the vessel, with a strong linear relationship (R 2 ~ 0.98) between lumen and total diameter for the gamut of vessels spanning from 10 to 150 μm in size (that is, all except the capillaries) .…”
Section: Scientific Advances With Ao Imaging: Vessel Structurementioning
confidence: 99%
“…48 Using AO retinal imaging, WLR can be measured non-invasively and has been shown to increase with mean blood pressure, body mass index and age. [49][50][51][52] The WLR in healthy individuals is highly predictable from the size of the vessel, with a strong linear relationship (R 2~0 .98) between lumen and total diameter for the gamut of vessels spanning from 10 to 150 μm in size (that is, all except the capillaries). 53 In hypertension the correlation remains strong but some vessels show significant departures from the predicted relationship, with narrowing of the lumen and concomitant thickening of the wall.…”
Section: Lumen and Vessel Wallmentioning
confidence: 99%